The applicability of agency theory to the management of media organizations in Iceland - Guðbjörg Hildur Kolbeins 1967- (2014)
It has previously been maintained by Napoli (1997) that agency theory (principal-agent approach) might be applied to media organizations to understand how media owners make sure that their companies are managed according to their wishes. Thus, the purpose of the present study was to investigate: a) whether the agency theory is applicable to four Icelandic media companies, and b) how the theory manifests itself in the management practices of these companies. The media companies that were examined were: the Icelandic National Broadcasting Service (RÚV), and three privately owned companies, i.e. 365 miðlar ehf., Árvakur hf. and DV ehf. Qualitative interviews were conducted with four editors-in-chief, two CEOs/publishers, the director general of RÚV and the news director of RÚV in May of 2012. Three of the interviewees were also part owners of the media companies. The results indicated that it is, indeed, possible to analyze management practices of media organizations from the perspective of agency theory. However, it varies how much the companies are driven by profit maximization, for instance; on which agency theory places an optimum emphasis. Also, the companies differ in their view towards other stakeholders like the public. The media house 365 ehf. turned out to be the best example of how the underlying constructs of agency theory are incorporated into the management practices of a media organization. Agency theory and stakeholder theory have generally been treated in the literature as being dichotomous. It is proposed in the present thesis that agency theory and stakeholder theory are not incompatible but rather should be reconceptualized as polar forces on the same continuum.